Atlas of clinical emergency medicine - Sherman, Scott C.; Cico, Stephen John; Nordquist, Erik; Ross, Christopher; Wang, Ernest (Wolters Kluwer, 2016)
A physician's time is limited in the ED, and lengthy paragraphs that take several sentences to make a management recommendation are no longer useful to the emergency physician at the point of care. This customer-focused Atlas allows emergency physician to quickly look up a diagnosis and make the appropriate management decisions in 3 minutes or less.